Analysis of Customer Relationship Management (CRM) Service Quality at the Surabaya City Population and Civil Registration Office - Faridah, Aisiah Cici; Moh. Musleh (Journal of Social and Policy Issues, 2025)
This study aims to analyze the quality of Customer Relationship Management (CRM) services at the Population and Civil Registration Service (Dispendukcapil) of Surabaya City based on five dimensions of service quality according to Zeithaml: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. By conducting this study, it is expected to obtain a comprehensive picture of the strengths and weaknesses of the CRM services implemented, as well as provide strategic recommendations for improving public services in the future. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the CRM services of the Surabaya City Dispendukcapil have provided good and diverse services, both online through social media, applications, email, and call centers, as well as offline at the Public Service Mall (MPP). In conclusion, the quality of CRM services at the Surabaya Dispendukcapil is classified as good with a high commitment to inclusive and technology-based public services. However, increasing technical capacity and system responsiveness is still needed to maintain the sustainability of optimal services.